PERILAKU KONSUMEN GENERASI Z DALAM ERA E - COMMERCE : STUDI KASUS TENTANG BELANJA ONLINE DALAM PERSPEKTIF EKONOMI ISLAM - Moh Agus Sifa' (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
Consumer behavior is a process related to how groups, individuals and organizations buy, select, use to meet needs. Generation Z are people born in the 1995-2010 range who grew up in an all-digital and advanced technology era that influenced their behavior and personality. It is necessary for marketers to know about consumer behavior in a complex manner in order to determine a good marketing strategy. The purpose of this study was to determine the consumer behavior of generation Z in purchasing online shopping from an Islamic economic perspective in the village of Binangun Singgahan, Tuban. The research method used in this research is a qualitative descriptive research method, by conducting structured interviews with generation Z in the village of Binangun Singgahan Tuban, so researchers use interview guidelines before going into the field and also use unstructured interviews to find out more about information that is not yet known. researchers when there are main questions that arise spontaneously. The results of this study indicate that there are three factors that influence generation Z consumer behavior in purchasing online shopping in the village of Binangun Singgahan, Tuban, namely time, price, and availability of goods. and The behavior of generation Z consumers in purchasing online shopping from an Islamic economic perspective is not appropriate because there are still those who carry out extravagant and extravagant actions.